Pentingnya Manajemen Sarana dan Prasarana di SMP Muhammadiyah 7 Yogyakarta - Deistyarini, Vidya Nendar; Setiawan, Farid; Fitri, Nurul Lahdila; Nabila, Jihan; Iqbal, Muhammad (Lembaga Yasin AlSys, 2022)
This study aims to reveal the implementation of services and management of infrastructure facilities managed in SMP Muhammadiyah 7 Yogyakarta. By using qualitative descriptive research whit sources of observation, interviews, and recording. The subjects of tgis study were the principal and vice principal of the infrastructure section. To support teaching and learning activities, it is very important to have infrastructure in schools, infrastructure has an important role to make teaching and learning activitiesmore effective so that it will create students who excel in knowledge.